The guilt trip - Fletcher, Anne, 1966-; Michaels, Lorne, 1944-; Goldwyn, John, 1958-; Goldberg, Evan.; Fogelman, Dan.; Streisand, Barbra; Najimy, Kathy; Rogen, Seth, 1982-; Paramount Pictures Corporation; Skydance Productions (Hollywood, CA : Paramount Pictures, 2013)
The plan for a quick stop at Mom's takes a turn when an impulse compels Andy to invite his mother, Joyce, on a three-thousand mile cross-country journey. But the further they go, the closer they get, and Andy realizes that they have more in common than he ever imagined.
Originally released as a motion picture in 2012.
Barbra Streisand, Kathy Najimy, Seth Rogen.
MPAA rating: PG-13; for language and some risque material.
DVD; NTSC, region 1; widescreen; 5.1 Dolby Digital.
English, French, or Spanish audio, with optional English, French, Portuguese or Spanish subtitles; English audio description; closed-captioned.
Keywords: Mothers and sons -- Drama; Voyages and travels -- Drama; Feature films; Road films; Comedy films; Video recordings for the hearing impaired; Video recordings for people with visual disabilities